2010
DOI: 10.1177/1088868310362982
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Differences in Expectations of Change and Tolerance for Contradiction: A Decade of Empirical Research

Abstract: Since the publication of Peng and Nisbett's seminal paper on dialectical thinking, a substantial amount of empirical research has replicated and expanded on the core finding that people differ in the degree to which they view the world as inherently contradictory and in constant flux. Dialectical thinkers (who are more often members of East Asian than Western cultures) show greater expectation of change in tasks related to explanation and prediction and greater tolerance of contradiction in tasks involving the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
321
3
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 306 publications
(355 citation statements)
references
References 108 publications
(205 reference statements)
29
321
3
2
Order By: Relevance
“…We developed 29 items, and then checked content validity using a panel of experts. Similar to validated scales of related constructs, we developed items that can be applied at work as well as in other contexts (e.g., Cialdini et al, 1995;Spencer-Rodgers et al, 2010;Webster & Kruglanski, 1994). Our panel of experts included four leading scholars familiar with methods of scale development as well as paradox theory.…”
Section: Study 1 Item Generation Exploratory Factor Analysis and Itementioning
confidence: 99%
See 1 more Smart Citation
“…We developed 29 items, and then checked content validity using a panel of experts. Similar to validated scales of related constructs, we developed items that can be applied at work as well as in other contexts (e.g., Cialdini et al, 1995;Spencer-Rodgers et al, 2010;Webster & Kruglanski, 1994). Our panel of experts included four leading scholars familiar with methods of scale development as well as paradox theory.…”
Section: Study 1 Item Generation Exploratory Factor Analysis and Itementioning
confidence: 99%
“…However, individuals may cognitively differentiate and integrate different perspectives but feel uncomfortable when the perspectives appear to be contradictory. Finally, research on naïve dialecticism, building on insights from Eastern philosophy, addresses individual attitudes towards contradictions (Choi et al, 2007;Spencer-Rodgers, Williams, & Peng, 2010), but not whether individuals accept and feel comfortable with contradictions. Similarly, the attitude towards contradictions subdimension of holism focuses on tactics for managing tensions, such as compromising and seeking middleground (Choi et al, 2007), rather than confronting and embracing tensions.…”
Section: Study 1 Item Generation Exploratory Factor Analysis and Itementioning
confidence: 99%
“…High dialectical thinkers tend to reconcile opposing views and contradictions by seeking the middle ground or accepting that both can exist simultaneously. In contrast, low dialectical thinkers tend to accept only one side as true while rejecting the other side (Spencer-Rodgers et al, 2010b). For example, Peng and Nisbett (1999) found that high dialectical thinkers (e.g., Chinese), relative to low dialectical thinkers (e.g., Americans), were more likely to accept two opposing statements as true; preferred dialectical proverbs that accept rather than deny contradictions (e.g., "Sorrow is born out of excessive joy") to nondialectical proverbs that reflect the rule on noncontradiction (e.g., "Half a loaf is better than none").…”
Section: Conflict Culture and Team Identitymentioning
confidence: 99%
“…I found that team cultural composition moderates the relation between conflict and team identity, and I argued that the reason why East Asian team's identity is not negatively influenced by high levels of conflict is because they endorse a stronger style of dialectical reasoning and can integrate the positive and negative aspects of conflict (Spencer-Rodgers et al, 2010b). Future research should directly measure and test dialectical reasoning.…”
Section: Limitations and Directions For Future Researchmentioning
confidence: 99%
“…Thus, theoretically related individual difference and cultural variables that may influence people's expectations for the four third culture forms were investigated. Specifically, predictions were developed and tested using theories on cognitive motivation (Cacioppo, Petty, Feinstein, & Jarvis, 1996;Earley & Ang, 2003;Kruglanski & Webster, 1996;Spencer-Rodgers, Williams, and Peng, 2010), multiculturalism ideology (Berry, 2003;Brodt et al, 2010;Verkuyten, 1995), national culture (Hofstede, 1980), and multicultural team experience.…”
Section: Field Study 2: Predictors Of Third Culture Expectationsmentioning
confidence: 99%